ANALASIS GESTUR SISWA SLOW LEARNER DALAM PEMBELAJARAN MATEMATIKA MENGGUNAKAN APLIKASI WORDWALL DI SDN BULU 02 MADIUN - Agestiningsih, Dian; Mochamad Nursalim (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Gesture is a non-verbal communication done with body or hand movements as a substitute for speech. Gestures function as an expression of a person's thoughts or feelings when interacting. This study aims to analyze the gestures of slow learner students in learning mathematics using the wordwall application in elementary schools. This study was conducted at SDN Bulu 02 using a descriptive qualitative approach method. The data collection techniques used were observation, interviews, documentation and student learning tests. By using data reduction, data presentation and drawing conclusions as data analysis techniques. This study concluded that deictic gestures are gestures that are widely used by students in the process of learning mathematics. The use of the wordwall application in the learning process can foster students' interest in learning and provide a sense of pleasure in the learning process.